Congenital tufted angioma: A multicenter retrospective study of 30 cases. Issue 6 (15th October 2018) - Feito‐Rodríguez, Marta; Sánchez‐Orta, Alba; De Lucas, Raúl; López‐Gutiérrez, Juan Carlos; Ruiz‐Bravo, Elena; Baselga, Eulalia; Victoria, Ana M.; Hernández‐Martín, Angela; Campos‐Domínguez, Minia; Berenguer Fröhner, Beatriz; Garnacho‐Saucedo, Gloria; Vera Casaño, Angel; et al.
Abstract: Background: Recent reports indicate that tufted angioma is a rare vascular neoplasm that manifests more frequently at birth than previously thought. Few studies specifically address congenital presentation. Objectives: We analyzed the clinicopathological characteristics, clinical course, and treatment of congenital tufted angioma (cTA) and evaluated variables that were indicative of problematic lesions. Methods: We performed an observational retrospective study of 30 patients with cTA in 9 Spanish hospitals over a 14‐year period. Histopathology and immunohistochemistry studies were performed. Results: Congenital tufted angioma mainly affected the limbs (56.67%), followed by the face and/or neck (23.33%). Almost three‐quarters of facial cTA were located over the mandibular area. Immunohistochemically, proliferating cells expressed markers of endothelial cells, with some clusters of cells, especially at the periphery of the aggregates, showing positivity for podoplanin. As no associated complications were observed in 66.67% of cases, no treatment was started. Limitations: Data were collected retrospectively. Conclusions: Our findings emphasize the clinical features and course of cTA. The possibility of cTA should be considered when a poorly defined congenital infiltrative vascular tumor with(out) overlying hirsutism appears over the mandibular area. Location on the face and/or neck requires a more comprehensive workup, since potentially severe complications often appear early.